2021
DOI: 10.3389/fphar.2021.662664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Real-Ambient PM2.5 Exposure on Lung Damage Modulated by Nrf2−/−

Abstract: Previous studies have shown that long-term exposure to fine particulate matter (PM2.5) increases the morbidity and mortality of pulmonary diseases such as asthma, chronic obstructive pulmonary disease and pulmonary emphysema. Oxidative stress and inflammation play key roles in pulmonary damage caused by PM2.5. Nuclear factor erythroid 2-related factor 2 (Nrf2) could regulate the expression of antioxidant and anti-inflammatory genes and is pivotal for protection against PM2.5-induced oxidative stress. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…In short, the IVC exposure system consists of a control and exposure chamber, which is connected to a three-layer HEPA filter to produce filtered air (FA), and an exposure chamber which is connected to unfiltered air (PM). The factors (temperature, airflow, humidity, pressure, ventilation frequency, air flow rate, and noise) in both chambers are consistent (Ding et al, 2021). Eight-week-old Nrf2 Knockout mice and WT mice were placed in FA and PM chambers (10 mice per group), and the mice were given food and water freely in a circulating chamber with 12 h light and 12 dark.…”
Section: Animal and Real-ambient Exposure Systemmentioning
confidence: 95%
See 2 more Smart Citations
“…In short, the IVC exposure system consists of a control and exposure chamber, which is connected to a three-layer HEPA filter to produce filtered air (FA), and an exposure chamber which is connected to unfiltered air (PM). The factors (temperature, airflow, humidity, pressure, ventilation frequency, air flow rate, and noise) in both chambers are consistent (Ding et al, 2021). Eight-week-old Nrf2 Knockout mice and WT mice were placed in FA and PM chambers (10 mice per group), and the mice were given food and water freely in a circulating chamber with 12 h light and 12 dark.…”
Section: Animal and Real-ambient Exposure Systemmentioning
confidence: 95%
“…Shijiazhuang City in Hebei Province experiences some of the most severe PM 2.5 pollution in China. The city's main sources of PM 2.5 are industrial emissions, vehicle exhaust, and coal burning (Zhang et al, 2021). Because of its severe pollution, we selected this city for our study.…”
Section: Pm 25 Exposure Induced Atr-dependent Dna Damage Repair In Ko...mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the upregulation of NRF2 expression may help prevent oxidative stress-related COPD progression. Interestingly, recent studies have shown that NRF2-deficient mice that were chronically exposed to particulate matter 2.5 had elevated oxidative stress and depressed ER stress levels but did not show obvious emphysema [ 144 ]. This may be attributed to the fact that the NRF2 deficiency reduces the expression of cytochrome P450 family 2 subfamily E member 1, thereby diminishing the cellular damage resulting from the metabolism of exogenous compounds [ 144 , 145 ].…”
Section: Copd and Er Stressmentioning
confidence: 99%
“…The real-ambient exposure system that was previously established in Shijiazhuang city was applied in this study ( Jiang et al, 2020 ; Ding et al, 2021 ). Compared to the concentrated ambient particle (CAP) exposure system, our system maintains the original chemical characteristics of PM2.5 and a concentration of PM2.5 similar to that of ambient PM2.5.…”
Section: Introductionmentioning
confidence: 99%